Inhibition of lipase and inflammatory mediators by Chlorella lipid extracts for antiacne treatment - G Sibi (Wolters Kluwer Medknow Publications, 2015)
Acne vulgaris is a chronic inflammatory disease, and its treatment is challenging due to the multifactorial etiology and emergence of antibiotic-resistant Propionibacterium acnes strains. This study was focused to reduce antibiotics usage and find an alternate therapeutic source for treating acne. Lipid extracts of six Chlorella species were tested for inhibition of lipase, reactive oxygen species (ROS) production, cytokine production using P. acnes (Microbial Type Culture Collection 1951). Lipase inhibitory assay was determined by dimercaprol Tributyrate - 5, 5'- dithiobis 2-nitrobenzoic acid method and ROS production assay was performed using nitro-blue tetrazolium test. The anti-inflammatory activity of algal lipid extracts was determined by in vitro screening method based on inhibition of pro-inflammatory cytokines, tumor necrosis factor-alpha (TNF-α) produced by human peripheral blood mononuclear cells. Minimum inhibitory concentration (MIC) values of lipid extracts were determined by microdilution method, and the fatty acid methyl esters (FAME) were analyzed by gas chromatography-mass spectroscopy. Chlorella ellipsoidea has the highest lipase inhibitory activity with 61.73% inhibition, followed by Chlorella vulgaris (60.31%) and Chlorella protothecoides (58.9%). Lipid extracts from C. protothecoides and C. ellipsoidea has significantly reduced the ROS production by 61.27% and 58.34% respectively. Inhibition of pro-inflammatory cytokines TNF-α showed the inhibition ranging from 58.39% to 78.67%. C. vulgaris has exhibited the MICvalue of 10 μg/ml followed by C. ellipsoidea, C. protothecoides and Chlorella pyrenoidosa (20 μg/ml). FAME analysis detected 19 fatty acids of which 5 were saturated fatty acids, and 14 were unsaturated fatty acids ranging from C14 to C24. The results suggest that lipid extracts of Chlorella species has significant inhibitory activity on P. acnes by inhibiting lipase activity. Further, anti-inflammatory reaction caused by the pathogen could be reduced by the inhibiting the production of ROS and inflammatory mediators TNF-α and exposes new frontiers on the antiacne activities of Chlorella lipid extracts.